2015
DOI: 10.1080/15374416.2015.1063428
|View full text |Cite
|
Sign up to set email alerts
|

Successful Therapist–Parent Coaching: How In Vivo Feedback Relates to Parent Engagement in Parent–Child Interaction Therapy

Abstract: Although behavioral parent training is considered efficacious treatment for childhood conduct problems, not all families benefit equally from treatment. Some parents take longer to change their behaviors and others ultimately drop out. Understanding how therapist behaviors impact parental engagement is necessary to improve treatment utilization. This study investigated how different techniques of therapist in vivo feedback (i.e., coaching) influenced parent attrition and skill acquisition in parent-child inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
46
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 23 publications
6
46
1
Order By: Relevance
“…Therefore, it is possible that the acquisition rate of PCIT skills is equally influenced by therapists’ and families’ variables. In the future, studies should examine how therapist behaviors (e.g., coaching styles; see Barnett et al 2015) interplay with families’ variables (e.g., language use, level of acculturation) to affect the acquisition rate of PCIT skills among Latino families.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the acquisition rate of PCIT skills is equally influenced by therapists’ and families’ variables. In the future, studies should examine how therapist behaviors (e.g., coaching styles; see Barnett et al 2015) interplay with families’ variables (e.g., language use, level of acculturation) to affect the acquisition rate of PCIT skills among Latino families.…”
Section: Discussionmentioning
confidence: 99%
“…Barnett et al (2015) found that parents who completed PCIT treatment received more frequent responsive/positive feedback in the first coaching session than parents who subsequently dropped out of treatment. No differences were found, however, in the frequency of directive or corrective feedback received by these parents (Barnett et al, 2015). As only one study to date has examined these associations, further investigation is critical.…”
mentioning
confidence: 92%
“…Barnett, Niec and Acevedo-Polakovich (2014) found that PCIT therapists’ frequency of responsive feedback in the second or third coaching session of PCIT was associated with parents’ frequency of labeled praises with their children during the next coaching session. In a different sample,Barnett et al (2015) found that PCIT therapists’ frequency of responsive feedback in the first coaching session predicted the number of sessions it took parents to attain skill mastery. Meade and Dozier (2012) found that ABC clinicians’ frequency of in the moment feedback in the third session of ABC predicted higher frequency of intervention-targeted parent behavior (i.e., following the child’s lead) in the ninth session, even when controlling for the parent’s prior level of this behavior.…”
mentioning
confidence: 97%
See 2 more Smart Citations